Studies on a Nigerian isolate of banana streak badnavirus: II. Effect of intraplant variation on virus accumulation and reliability of diagnosis by ELISA - Dahal, G.; Pasberg-Gauhl, C.; Gauhl, F.; Thottappilly, G.; Hughes, J. (Wiley, 1998)
Monitoring of banana streak badnavirus (BSV) antigens and symptoms in naturally BSV‐infected plantain and banana (Musa spp.) plants showed a great variation in symptom expression, distribution and relative concentration of BSV between and within plants. Expression and distribution of symptoms was erratic within individual leaves as well as between different leaves of the same plant. The concentration of BSV antigens detected by triple antibody sandwich enzyme linked immunosorbent assay (TAS‐ELISA) varied in different plant parts including leaf lamina, midrib and pseudostem, roots and young ‘cigar' leaf. The concentration of BSV antigens was high in symptomatic tissues but was low or below the limits of detection in most asymptomatic tissues. During ‘hot dry' seasons when symptoms were not fully expressed, the concentration of BSV antigens in leaf tissues declined drastically, often below the detection limit of TAS‐ELISA. These results suggested that for more reliable detection of BSV antigens by TAS‐ELISA, it is advisable to index plants using composite tissue samples comprising as many leaves as possible for each plant and collected during cool and/or rainy seasons when symptom expression is generally severe.